A heat-insulating fireproof material and its use
Through the composite material of porous materials and hollow particles, combined with the sealing layer and the heat storage layer, the existing thermal insulation and fire-repellent materials have been solved, and lightweight and efficient heat insulation is achieved to ensure that under high temperature environments Thermal insulation performance provides safety protection.
Patent Information
- Application Number
- CN202080044134.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-25
- Filing Date
- 2020-07-03
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-07-03
AI Technical Summary
In the application of existing heat-insulating and fire-resistant materials in electric vehicle battery cells, there are problems such as large weight, large volume, poor thermal conductivity and poor compression elasticity, which are difficult to achieve lightweight and effective heat insulation, and their performance is degraded in high-temperature environments.
Porous materials and hollow particles composite materials are used to combine the sealing layer and the heat storage layer to form a heat-insulating and fire-resistant material with low thermal conductivity. After carbonization treatment, the thermal conductivity is controlled below 0.040W/(m·K to ensure that the material is in a high-temperature environment. and improve mechanical properties through aerogel powder and fiber structures.
It achieves a combination of heat insulation and fire resistance, and is lightweight. It can effectively block heat energy transfer, extend escape time, provide safety protection, and maintain good thermal insulation performance in high temperature environments.
Smart Images

Figure CN113939942B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a heat-insulating fireproof material and application thereof. Background Art
[0002] In traditional electric vehicle power batteries, heat insulation and fireproof materials are generally formed by high temperature resistant flame retardant inorganic materials, such as mica materials. However, due to the large specific gravity of mica, when used as a heat insulation sheet between two battery cells in actual use, the overall weight of the battery increases, which is not conducive to the lightweight of electric vehicles, thereby affecting the range of electric vehicles.
[0003] Although increasing the number of batteries within a certain range can increase the range of electric vehicles, the number of batteries is restricted due to the limited volume and weight of the vehicle. In order to achieve the purpose of increasing the range, the battery capacity should be increased while the volume and weight remain unchanged, that is, the energy density of the battery should be increased. However, it is difficult to increase the energy density of electric vehicle batteries.
[0004] In addition, mica sheets are hard and brittle, and are extremely difficult to compress in the thickness direction. When the battery is in use or charging, the cell expands in the thickness direction, and the mica sheets are squeezed but difficult to compress. Although mica materials have good heat resistance, their thermal conductivity is poor. Therefore, it is necessary to develop a material that has both heat insulation and fire prevention effects and good compression resilience, and can withstand dimensional changes caused by deformation of the cell even under the influence of temperature.
[0005] For example, Japanese Patent Publication No. 2018-179010 discloses a fire-resistant heat-insulating sheet. Since the invention places a layered insulation body in a bag made of refractory fibers, it will vibrate or compress under external forces during use. Under shearing, the insulation body and the bag will separate, and it is impossible to ensure that the entire sheet can play a heat-insulating role. In addition, the surface of inorganic fibers is smooth and rigid, the entanglement force between the fibers that constitute the non-woven fabric is small, and the adhesion of aerogel is unstable, resulting in poor overall mechanical properties of the insulation body. Moreover, the inorganic fibers themselves have a high density and are difficult to bend. The non-woven fabric formed has a high gram weight and a large thickness, which results in the overall weight and volume of the fire-resistant heat-insulating sheet, making it impossible to achieve lightweighting. In addition, although silica-based inorganic fibers containing hydroxyl groups are used in the insulation body, Si(OH) is heated to form a non-woven fabric. 4 Dehydration condensation reaction occurs to generate H 2 O, but because the water generated by the reaction is very limited, no significant endothermic cooling effect can be obtained.
[0006] For example, Japanese Patent Laid-Open No. 2018-118489 discloses an aerogel layered composite and thermal insulation material. Since the aerogel in this invention is distributed in layers alone and lacks a substrate for supporting and reinforcing, it is easily compressed and deformed when squeezed by external force, and the compressed part cannot recover after the external force is removed.
[0007] For example, China's patent CN207425974U discloses a thermal runaway blocking protective sheet for a battery box. Due to the low bonding strength of the polymer film layer around the fiber felt, the battery cell vibrates when the car is running and rubs against the flame-retardant insulation felt, causing the edge of the polymer film layer to peel off and the aerogel powder therein to fly, thereby reducing the thermal insulation performance of the protective sheet. In addition, the protective sheet also includes an explosion-proof layer made of metal material as a packaging layer, which increases the overall weight of the protective sheet and makes it difficult to achieve lightweight.
[0008] Another example is the Chinese patent CN108689678A, which discloses a fiber-reinforced aerogel felt with no large aerogel particles attached to the surface and a preparation method thereof. In the invention, the fiber felt has a small overall specific gravity and large and numerous pores, and aerogel particles are difficult to attach. Even after attachment, aerogel particles are prone to fall off, thereby affecting the thermal insulation performance of the material. Moreover, the invention adopts the whole roll normal pressure impregnation method, which will lead to poor dispersion uniformity of aerogel in the rolled fiber felt, and uneven impregnation of the outer layer and the inner layer, thereby affecting the stability of the thermal insulation performance of the felt. Summary of the invention
[0009] The object of the present invention is to provide a heat-insulating fireproof material with good flame retardancy, high temperature resistance, small thermal conductivity and light weight.
[0010] The technical solution of the present invention is as follows: The heat-insulating fireproof material of the present invention contains at least a heat-insulating layer, wherein the heat-insulating layer contains a porous material and hollow particles, and the volume density of the porous material is 0.05 to 0.30 g / cm 3 The average diameter of the hollow particles is 30 to 1000 μm, and the thermal conductivity of the heat insulating and fireproofing material after carbonization is less than 0.040 W / (m·K) at room temperature.
[0011] The above-mentioned thermal insulation and fireproofing material also contains a sealing layer, which is a continuous sheet material. The sealing layer is located on at least two opposite sides of the thermal insulation layer, and the average total thickness of the sealing layer accounts for 0.5-90% of the overall thickness of the thermal insulation and fireproofing material.
[0012] The above-mentioned heat insulating fireproof material also contains a heat storage material, which is a hydrate or a metal hydroxide. The weight ratio of the water released by the heat storage material when heated to the weight ratio of the heat insulating fireproof material is preferably 2.0-25.0%.
[0013] The heat storage material is preferably in a layered structure distributed on two opposite sides of the heat insulation layer, and the ratio of the average thickness of the heat storage layer to the average thickness of the heat insulation layer is preferably 10-90%.
[0014] The above-mentioned heat storage material is preferably dispersed in the heat insulating layer.
[0015] The above-mentioned heat storage material is preferably dispersed in the sealing layer.
[0016] The porous material is preferably a fiber structure.
[0017] In the fiber structure, pores having a pore size of 5 to 50 μm preferably account for more than 50% of all pores.
[0018] The thermal conductivity of the fiber structure is preferably lower than 0.040 W / (m·K) at room temperature.
[0019] The fiber structure is preferably a nonwoven fabric comprising thermoplastic fibers having an LOI value of 28% or more and non-melting fibers.
[0020] The hollow fine particles are preferably aerogel powder.
[0021] The weight ratio of aerogel powder in the heat insulating and fireproofing material of the present invention is preferably 15% or more.
[0022] The air tightness of the continuous sheet material is preferably within 20 cm 3 / cm 2 / s or less.
[0023] The above-mentioned continuous sheet material is preferably a film-like material, a sheet material formed of a fiber textile, or a sheet material formed of a continuous resin.
[0024] The temperature difference between the two surfaces of the heat insulating and fireproofing material of the present invention is preferably greater than 300°C.
[0025] Beneficial effects of the present invention: The heat-insulating and fire-proofing material of the present invention has excellent heat-insulating and fire-proofing properties and is lightweight. The heat-insulating and fire-proofing material of the present invention can be used between the cells of a power battery as a buffer heat-insulating material, can effectively block the transfer of heat energy, and is fire-retardant, slowing down the transfer speed of the huge heat and flame when the cell explodes, and slowly transferring the heat to adjacent cells, thereby extending the escape time of the driver and passengers and playing a role in safety protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a schematic diagram of the heat-insulating and fire-proofing material of the present invention. In the figure, A is the heat-insulating layer, B is the heat-storage layer, and C is the sealing layer. The heat-storage layer B is distributed on both sides of the heat-insulating layer A, wherein a is a porous material, b is a hollow particle, c is a continuous sheet material, and d is a heat-storage material.
[0027] Figure 2 This is a schematic diagram of the heat-insulating and fire-proofing material of the present invention. In the figure, A is the heat-insulating layer, B is the heat-storage layer, and C is the sealing layer. The heat-storage layer and the sealing layer are the same layer, wherein a is a porous material, b is a hollow particle, c is a continuous sheet material, and d is a heat-storage material.
[0028] Figure 3 This is a schematic diagram of the heat-insulating and fire-proofing material of the present invention. In the figure, A is the heat-insulating layer, B is the heat-storage layer, and C is the sealing layer. The heat-insulating layer and the heat-storage layer are the same layer, wherein a is a porous material, b is a hollow particle, c is a continuous sheet material, and d is a heat-storage material. DETAILED DESCRIPTION
[0029] The heat insulating fireproof material of the present invention at least comprises a heat insulating layer, wherein the heat insulating layer comprises a porous material and hollow particles, wherein the volume density of the porous material is 0.05 to 0.30 g / cm 3 , the average diameter of the hollow particles is 30 to 1000 μm, and the thermal conductivity of the heat insulating and fireproofing material after carbonization is less than 0.040 W / (m·K). Porous materials refer to materials with a mesh structure composed of mutually interpenetrating or closed holes, and the material has a certain thickness. For example, the porous material is a foam porous material, a metal powder sintered porous material, a fiber structure, etc., and a fiber structure is preferred because the fiber structure has good compression recovery and is compressed and deformed by external force. After the external force is removed, the fiber structure can recover quickly and eliminate the compression deformation. Hollow particles refer to particulate matter with a hollow structure or cavity, wherein the cavity can be completely closed or partially closed. If the hollow particles are hollow silica particles, hollow glass beads, hollow ceramic particles, etc., hollow silica particles, i.e., silica aerogel particles, are preferred because hollow silica particles have high porosity, high specific surface area, and light weight, and have excellent thermal insulation properties. Silica aerogel powder with appropriate particle size maintains the nanoporous structure of aerogel, which makes it easier to disperse and fill, and then compound with porous materials. That is, hollow particles can be effectively contained and attached to porous materials containing holes to form a network structure. The porous material provides support for the hollow particles, making them integrated into a thermal insulation layer. The resulting thermal insulation layer has certain mechanical strength and functionality, such as fire prevention and heat insulation.
[0030] The bulk density of the porous material of the present invention must be controlled within a certain range. If the bulk density of the porous material is lower than 0.05 g / cm3 If the porous material has too many pores, or even large through-holes, the hollow particles attached to the porous material will fall out of the large pores, and the hollow particles may not be accumulated, and the resulting insulation layer will not have a good insulation effect. If the volume density of the porous material is higher than 0.30 g / cm 3 If the porous material is too dense, the pores in the porous material will become smaller and fewer, the adhesion of hollow particles will decrease, and they may even be unable to enter the interior of the porous material, which will greatly reduce the thermal insulation performance of the thermal insulation layer. Since hollow particles have a hollow or cavity structure, they can store air. Hollow particles of appropriate particle size adhere to and accumulate in porous materials, which can greatly reduce the barrier property of the thermal insulation and fireproof material of the present invention to heat transfer. If the average diameter of the hollow particles is less than 30 μm, the contact area between the hollow particles dispersed in the porous material and the porous material becomes smaller, resulting in difficulty in the attachment of the hollow material, and the particles are prone to scattering and falling, thereby causing a decrease in thermal insulation performance; if the average diameter of the hollow particles is greater than 1000 μm, large-particle hollow particles are difficult to enter the internal pores of the porous material, but only float on the surface of the porous material, and are prone to scattering and falling during use, and the thermal insulation performance is greatly reduced. Moreover, since the particle size of the hollow particles is too large, the dispersion of the hollow particles in the porous material becomes extremely uneven, thereby causing the uniformity of the overall thermal insulation performance of the material to deteriorate. Considering the dispersion stability and thermal insulation uniformity of the hollow particles, the average diameter of the hollow particles is preferably 50 to 800 μm, more preferably 50 to 500 μm. The average diameter of the hollow particles here, for aerogel particles, refers to the particle size of the aggregate formed by the three-dimensional spatial network structure of the aerogel.
[0031] The thermal conductivity of the heat-insulating fireproof material of the present invention after carbonization treatment is less than 0.040W / (m·K). As a heat-insulating material used between battery cells, it can effectively delay or block the thermal runaway of the battery cell, thereby delaying the time of heat transfer to the entire battery system. Therefore, the heat-insulating fireproof material must have excellent thermal insulation, especially when the battery cell is in thermal runaway, the heat-insulating fireproof material will be instantly carbonized by high temperature. At this time, the heat-insulating fireproof material is required to maintain good thermal insulation performance after carbonization, so as to avoid chain runaway. If the thermal conductivity of the heat-insulating fireproof material after carbonization treatment is higher than 0.040W / (m·K), that is, when the heat-insulating material is carbonized at high temperature, its thermal conductivity becomes higher, and the high temperature generated by the battery cell in thermal runaway cannot be blocked, and a heat diffusion reaction occurs, causing rapid heat transfer, and further quickly conduction The heat is transferred to the adjacent battery cell, causing the adjacent battery cell to instantly have a chain thermal runaway, further exacerbating the battery combustion speed, reducing the precious escape time of the driver and passengers, and even causing serious casualties. Taking into account the volume density of the porous material and the content of hollow particles in the heat-insulating and fire-proofing material, the thermal conductivity of the heat-insulating and fire-proofing material of the present invention after carbonization treatment is preferably 0.020 to 0.040 W / (m·K) at room temperature.
[0032] The heat-insulating fireproof material of the present invention preferably contains a sealing layer, the sealing layer is a continuous sheet material, the sealing layer is located on at least two opposite sides of the heat-insulating layer, and the average total thickness of the sealing layer accounts for 0.5 to 90% of the overall thickness of the heat-insulating fireproof material. Since hollow particles are attached to the porous material in the heat-insulating layer, during the packaging, transportation and use of the heat-insulating material, the hollow particles are easily scattered and dropped by external forces, which directly affects the heat-insulating performance of the material. When the material is used as a heat-insulating buffer material between the battery cores, the heat-insulating property deteriorates or is uneven. Once the battery core is abnormally heated, the heat transfer cannot be effectively blocked in time, resulting in thermal runaway of the battery core. In severe cases, it will cause the driver and passengers to have no time to escape, causing major casualties. Therefore, it is preferred to set a sealing layer on at least two opposite sides of the heat-insulating layer, and the sealing layer is a continuous sheet material, so that the hollow particles in the heat-insulating layer can be effectively prevented from scattering, and the heat-insulating performance can be maintained to the greatest extent. Since the heat-insulating layer is a material with a certain thickness, it can be regarded as a cuboid. Therefore, the sealing layer can be located on two opposite sides of the thermal insulation layer, or on four or six sides of the thermal insulation layer. When the sealing layer is located on two opposite sides of the thermal insulation layer, the two sides are the two opposite sides with the largest area on the rectangular thermal insulation layer, that is, the upper and lower surfaces of the thermal insulation layer. This can not only prevent the hollow particles in the thermal insulation layer from scattering or falling off due to external vibration or extrusion, but also can be produced quickly and at low cost. When the sealing layer is located on four or six sides of the thermal insulation layer, that is, the sealing layer not only covers the upper and lower surfaces of the thermal insulation layer, but also covers the sides of the thermal insulation layer. At this time, the hollow particles in the thermal insulation layer can be completely prevented from scattering or falling off due to external vibration or extrusion. Therefore, it is more preferred that the sealing layer is located on four or six sides of the thermal insulation layer.
[0033] When the sealing layer is a film-like material, the average thickness of the sealing layer is preferably 5 to 200 μm. If the average thickness of the film-like material is too thin, it is easy to be damaged by the thermal expansion, extrusion and friction between the battery cells on both sides, causing the hollow particles in the thermal insulation layer to fly and fall, resulting in a decrease in thermal insulation; if the average thickness of the film-like material is too thick, due to the high density, the compressible space is too small, and even after being compressed, its resilience is poor. When the battery cell cools and restores its original thickness, the thermal insulation and fireproof material as a whole cannot return to its original thickness, resulting in gaps between adjacent battery cells and loosening of the thermal insulation and fireproof material.
[0034] When the sealing layer is a fiber textile, the average thickness of the sealing layer is preferably 100 to 400 μm. If the thickness of the fiber textile is too thin, it is easy to be damaged by the thermal expansion, extrusion and friction between the battery cells on both sides, causing the hollow particles in the thermal insulation layer to scatter and fall, resulting in a decrease in thermal insulation; if the thickness of the fiber textile is too thick, since the overall thickness of the thermal insulation and fireproof material is limited, generally not more than 4 mm, the thickness of the thermal insulation layer or the heat storage layer can only be reduced, resulting in a decrease in the overall performance of the thermal insulation and fireproof material. In particular, a high-density flame-retardant fiber textile with a thickness of 100 to 200 μm is preferably used as a sealing layer, which can not only prevent the hollow particles in the thermal insulation layer from scattering and falling, but also improve the deformation resistance and shear resistance of the thermal insulation and fireproof materials, and even play a role in flame retardancy and fire prevention. When the battery cell catches fire, it can block the spread of flames and slow down heat transfer.
[0035] When the sealing layer is a sheet material formed by resin, since the sheet material formed by the resin contains heat storage materials, the more heat storage materials contained, the higher the thickness of the sheet material formed by the resin. For thermal insulation and fireproof materials, the more heat is absorbed. Considering the overall thickness of the thermal insulation and fireproof materials, the average thickness of the sealing layer is preferably 200 to 1000 μm. If the thickness of the sheet material formed by the resin is too thin, since the heat storage material contained in the resin layer is too little, the amount of heat that can be absorbed becomes less, resulting in a decrease in the overall thermal insulation of the thermal insulation and fireproof materials; if the thickness of the sheet material formed by the resin is too thick, since the overall thickness of the thermal insulation and fireproof materials is limited, generally not exceeding 4 mm, the thickness of the thermal insulation layer becomes thinner, the thermal insulation performance decreases, and the overall thermal insulation performance of the thermal insulation and fireproof materials also decreases.
[0036] The average total thickness of the sealing layer preferably accounts for 0.5 to 90.0% of the overall thickness of the thermal insulation and fireproofing material. The average total thickness of the sealing layer in the present invention refers to the sum of the average thicknesses distributed on the upper and lower surfaces of the thermal insulation layer. The overall thickness of the thermal insulation and fireproofing material refers to the distance between the upper and lower surfaces of the thermal insulation and fireproofing material of the present invention, that is, it includes all the thicknesses of the thermal insulation layer, the heat storage layer and the sealing layer. The ratio of the average total thickness of the sealing layer to the overall thickness of the thermal insulation and fireproofing material can reflect the sealing performance of the sealing layer to the hollow material on the one hand, and directly affect the overall compression recovery performance of the thermal insulation and fireproofing material on the other hand. If the average total thickness of the sealing layer accounts for too low a proportion of the overall thickness of the thermal insulation and fireproofing material, it means that the sealing layer is too thin. When the obtained thermal insulation and fireproofing material is installed between battery cells, the vibration of the battery cells on both sides and the friction generated can easily destroy the continuity of the too thin sealing layer, causing the hollow particles evenly dispersed inside the porous material to fall due to external forces such as vibration, and the hollow particles to scatter from the pores of the porous material, resulting in a decrease in the amount of hollow particles attached and uneven distribution. When the battery cell has thermal runaway, it cannot play a good role in thermal insulation and fireproofing, leading to The heat is quickly transferred to the adjacent battery cells, causing a chain reaction; if the average total thickness of the sealing layer accounts for too high a proportion of the overall thickness of the thermal insulation and fireproofing material, it means that the sealing layer is too thick. When the obtained thermal insulation and fireproofing material is installed between the battery cells, it is squeezed by the battery cells that are thermally expanded on both sides. The overly thick sealing layer has a high density and a small compressible space. Even after being compressed, its resilience is poor. When the battery cell cools and restores its original thickness, the thermal insulation and fireproofing material as a whole cannot return to its original thickness, resulting in gaps, loosening of the battery cell, and even deformation and failure of the battery cell. On the other hand, if the average total thickness of the sealing layer accounts for too high a proportion of the overall thickness of the thermal insulation and fireproofing material, that is, the thickness of the thermal insulation layer is too thin, and there are too few porous materials and hollow particles in the thermal insulation layer as the thermal insulation body, which cannot provide sufficient thermal insulation performance for the material. When the obtained thermal insulation and fireproofing material is installed between the battery cells, it cannot play a good thermal insulation and fireproofing effect when the battery cell has thermal runaway, causing the heat to be quickly transferred to the adjacent battery cells, causing a chain reaction. Taking into account the performance requirements of thermal insulation, fireproofing, cushioning and shock absorption, and lightweight of thermal insulation and fireproofing materials, as well as the sealing and compression resilience when used between battery cells, the average total thickness of the sealing layer of the present invention accounts for a proportion of the overall thickness of the thermal insulation and fireproofing material that is more preferably 10.0-70.0%, and further preferably 25.0-50.0%.
[0037] The thermal insulation and fireproofing material of the present invention preferably contains a heat storage material. The heat storage material can make up for the limitation of the heat insulation layer in the thermal insulation and fireproofing material on the heat barrier effect. In particular, when the thermal insulation and fireproofing material is in an environment where the temperature rises sharply, the heat storage material can effectively suppress the temperature rise. The heat storage material is a hydrate or a metal hydroxide. The weight of the water released by the thermal storage material when heated is preferably 2.0 to 25.0% relative to the weight of the thermal insulation and fireproofing material. Hydrate refers to a compound containing water, usually refers to a crystalline hydrate, that is, a substance containing a certain amount of crystal water, and its source is quite wide. The water in the hydrate can be connected to other parts by coordination bonds, such as hydrated metal ions, and the chemical formula is KAl(SO 4 ) 2 12H 2 O, or it can be combined by covalent bonds, such as hydrated chloroacetaldehyde. Some crystalline hydrates can automatically lose part or all of their crystalline water at room temperature and in dry air. This phenomenon is called weathering. Therefore, such crystalline hydrates do not exist at room temperature because of the loss of water. Some crystalline hydrates need to be heated to occur. When the hydrate is heated, hydrolysis or dehydration reactions will occur, that is, water molecules are lost by heating. The loss of water molecules can occur inside the compound molecule, that is, intramolecular dehydration, or between two molecules of the same compound, that is, intermolecular dehydration. During the dehydration process, the water in the hydrate undergoes an endothermic reaction and can absorb heat, thereby reducing heat conduction. Metal hydroxide refers to an inorganic compound formed by a metal cation and a hydroxide ion (-OH). When heated, it can generate metal oxides and water, which can absorb heat. Because the decomposition temperatures of metal hydroxides vary greatly, such as Al(OH) 3 The thermal decomposition starting temperature is about 220℃, Mg(OH) 2The starting temperature of thermal decomposition is about 340°C, while NaOH is difficult to be decomposed by heating. This is related to the metallic properties of the metal in the metal hydroxide. Generally speaking, the stronger the metallic property, the higher the stability of the hydroxide. Considering the actual application environment of the heat-insulating and fire-proof material of the present invention, metal hydroxides with a decomposition temperature of 100 to 1200°C are preferred, such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, etc. In addition, from the perspective of thermal storage density, not only the decomposition temperature in the range of 100 to 1200°C is preferred, but also the metal hydroxides with a thermal storage density of more than 600kJ / kg, such as aluminum hydroxide, are further preferred. The thermal storage density here can characterize the ability of a material per unit weight to absorb heat. If the thermal storage density of the thermal storage material is too low, it will not be able to absorb the large amount of heat generated by the battery core when it contacts the battery core with a sharp rise in temperature. The thermal storage material quickly absorbs heat to saturation and no longer absorbs heat. It cannot effectively delay the increase in the temperature of the battery core, thereby affecting the overall thermal insulation performance of the material. Considering the overall quality and thermal insulation performance of the sample after composite processing, the thermal storage density of the chemical thermal storage material is more preferably above 1000kJ / kg.
[0038] The weight ratio of the water released by the above-mentioned heat storage material when heated to the weight ratio of the heat insulating fireproof material is preferably 2.0-25.0%. If the weight ratio of the water released by the heat storage material when it is thermally decomposed to the weight ratio of the heat insulating fireproof material is too low, the water released after being heated can absorb less heat, that is, thermal decomposition can occur under relatively low heat conditions. However, when such heat storage materials are used between battery cells, if the battery cells heat up abnormally and cause thermal runaway, when the heat storage materials contact the battery cells with rapidly rising temperatures, they cannot quickly absorb the large amount of heat energy generated by the battery cells, and thus cannot Effectively block the transfer of heat to adjacent cells, and in severe cases, chain explosions occur; if the weight of the water released by the heat storage material when heated is too high relative to the weight of the heat insulation and fireproof material, the weight ratio of the heat insulation layer as the heat insulation body must decrease, that is, the weight ratio of the porous material and the hollow particles in the heat insulation layer decreases, which directly leads to a decrease in the overall heat insulation performance of the heat insulation and fireproof material, and thus cannot provide sufficient heat insulation performance. When the prepared heat insulation and fireproof material is installed between the cells, the heat insulation effect is poor, resulting in more heat being quickly transferred to the adjacent cells, a chain reaction occurs, and the battery as a whole has thermal runaway. Considering the overall heat insulation and lightweight of the heat insulation and fireproof material, the weight ratio of the water released by the above-mentioned heat storage material when heated relative to the weight of the heat insulation and fireproof material is more preferably 5-20%.
[0039] The heat insulating and fireproofing material of the present invention preferably contains a heat storage material, and the heat storage material is present in the heat insulating and fireproofing material in the following manner.
[0040] Method 1: Mix the heat storage material with heat-meltable solid flame-retardant adhesive particles to obtain mixed particles, and spread the mixed particles evenly on the upper and lower surfaces of the pre-prepared thermal insulation layer in a spreading manner to form a layer of heat storage powder layer in the form of a film, i.e., the heat storage layer, and then use a continuous sheet material to encapsulate at least two opposite sides, and preliminarily consolidate the two by heating, melting, cooling and solidifying to form a heat storage layer distributed on both sides of the thermal insulation layer, and encapsulated by the continuous sheet material into an integrated thermal insulation and fireproof material.
[0041] Method 2: Evenly mix the heat storage material and liquid flame retardant resin to form a flame retardant resin liquid of the heat storage material, and then evenly apply it to the upper and lower surfaces of the pre-prepared thermal insulation layer, dry and solidify at a suitable temperature, and then cool at room temperature to form a flame retardant resin solidified film with heat storage material powder attached on both sides of the thermal insulation layer, and finally obtain a thermal insulation and fireproof material with the heat storage layer and the sealing layer integrated in the heat storage layer, where the heat storage layer is distributed on both sides of the thermal insulation layer. At this time, the heat storage layer is the sealing layer. The flame retardant resin solidified film with heat storage material particles attached can not only absorb a large amount of heat, but also solve the problem of hollow particles inside the porous material scattering out of the pores of the porous material.
[0042] Method three: Sprinkle the heat storage material powder into a pre-prepared porous material containing hollow particles, and use physical filling to make the heat storage material powder fully enter the gaps between the porous material and the hollow particles to obtain a heat insulation layer, which is also a heat storage layer. Then use a continuous sheet material to encapsulate at least two opposite sides to form a heat insulation and fireproof material in which the heat insulation layer and the heat storage layer are the same layer structure and are encapsulated as a whole by the continuous sheet material.
[0043] The preparation method of the heat-insulating fireproof material of the present invention is not limited to the above three methods, and the above three methods can also be used interchangeably to obtain a heat-insulating fireproof material that has both heat-insulating and fireproof properties and is lightweight.
[0044] The heat storage material of the present invention is preferably a layered structure distributed on opposite sides of the heat insulation layer, and the ratio of the average thickness of the heat storage layer to the average thickness of the heat insulation layer is preferably 10 to 90%. The heat storage layer is preferably distributed on opposite sides of the heat insulation layer. Since the heat insulation layer has a certain thickness, it can be regarded as a rectangular parallelepiped. The opposite sides of the heat insulation layer refer to the opposite sides of the rectangular heat insulation layer with the largest area, that is, the upper and lower surfaces. The opposite sides of the heat insulation layer are in direct surface contact with the battery cell. Once the battery cell has thermal runaway, it can most effectively block the heat from the battery cell, thereby delaying the thermal runaway of the adjacent battery cell and avoiding a chain reaction. If the ratio of the average thickness of the heat storage layer to the average thickness of the insulation layer is too low, that is, the average thickness of the heat storage layer accounts for too small a proportion, the heat storage material that plays a role in heat storage in the heat storage layer is less, and the heat that can be absorbed when decomposed by heat is also sharply reduced, so it cannot absorb heat and inhibit the temperature rise, and can only rely on the insulation effect of the insulation layer, which cannot fully block the heat conduction, so that the adjacent battery cells are heated and heated and thermal runaway occurs; if the ratio of the average thickness of the heat storage layer to the average thickness of the insulation layer is too high, that is, the average thickness of the insulation layer accounts for too small a proportion, the thickness of the insulation layer is too thin, and the content of porous materials and hollow particles contained in the insulation layer as the insulation body is too small, especially after the content of hollow particles is reduced, the through pores contained in the porous material may be directly exposed, and the high temperature heat on one side will be directly transferred to the opposite side through the pores, and the heat cannot be effectively blocked. Moreover, when the thickness of the insulation layer is too thin, that is, the thickness of the layer where the hollow particles are located is too thin, the air barrier layer that can be formed by the hollow particles becomes thinner. As we all know, air is an excellent thermal insulation material. When the air barrier layer becomes thinner, the heat barrier effect becomes worse, that is, heat can be easily transferred from one side of the thermal insulation layer to the other side. When the prepared thermal insulation and fireproof material is installed between battery cells, when the battery cell has thermal runaway, the too thin thermal insulation layer cannot play a good thermal insulation and fireproof effect, causing the heat to be quickly transferred to the adjacent battery cells, causing a chain thermal runaway reaction. Taking into account the thermal insulation and fireproofing, buffering and shock absorption of the thermal insulation and fireproofing materials, as well as the sealing and compression resilience when used between battery cells, the ratio of the average thickness of the above-mentioned heat storage layer to the average thickness of the thermal insulation layer is more preferably 15-85%.
[0045] The average thickness of the above-mentioned heat storage layer is preferably 100-2000 μm. When the heat storage layer is a layered structure distributed on opposite sides of the heat insulation layer, the thickness of the heat storage layer on each side is preferably 50-1000 μm. The more heat storage materials contained in the heat storage layer, the thicker the heat storage layer formed, and the more heat is absorbed, but the thickness of the heat insulation and fireproof material finally obtained is also higher. Considering the overall thickness of the heat insulation and fireproof material, when the heat storage material is mixed with heat-meltable solid flame-retardant adhesive particles to obtain mixed particles, and is evenly spread on the upper and lower surfaces of the pre-prepared heat insulation layer in a spreading manner, the thickness of the heat storage layer on one side is more preferably 50-200 μm. When the heat storage material is dispersed in the flame-retardant resin and is also located on both sides of the heat insulation layer as a sealing layer, the thickness of the heat storage layer on one side is preferably 200-1000 μm. If the thickness of the heat storage layer on one side is too thin, since it contains too little heat storage material, it will not be able to absorb the large amount of heat generated by the battery cell when it comes into contact with the battery cell whose temperature rises sharply. The heat storage material will quickly become saturated and will no longer absorb heat. It will not be able to effectively delay the increase in the temperature of the adjacent battery cells, resulting in a decrease in the overall thermal insulation of the thermal insulation and fireproofing material.
[0046] The average thickness of the above-mentioned thermal insulation layer is preferably 600 to 2400 μm. The thermal insulation layer contains porous materials and hollow particles, which play an important role in thermal insulation in thermal insulation and fireproof materials. If the thickness of the thermal insulation layer is too thin, when the thermal insulation and fireproof material is used between battery cells as a thermal insulation buffer material, once the battery cell is abnormally heated during use, it will not be able to effectively block the transfer of heat in time, resulting in continuous thermal runaway of the battery cell. In severe cases, it will cause the driver and passengers to have no time to escape, causing major casualties; if the thickness of the thermal insulation layer is too thick, it is necessary to adjust it by reducing the thickness of the heat storage layer or the sealing layer. After the thickness of the heat storage layer is reduced, when it contacts the battery cell with a sharply rising temperature, it cannot absorb the large amount of heat energy generated instantly.
[0047] The present invention preferably disperses the heat storage material in the heat insulation layer. When the heat insulation fireproof material is obtained by the above method three, the heat storage material powder is sprinkled into the pre-prepared porous material containing hollow particles, and the heat storage material powder is fully entered into the gap between the porous material and the hollow particles by physical filling to obtain a heat insulation layer, which is also a heat storage layer. Then, a continuous sheet material is used to encapsulate at least two opposite sides to form a heat insulation layer and a heat storage layer. The heat insulation layer and the heat storage layer are the same layer structure, and the heat insulation fireproof material is encapsulated as a whole by the continuous sheet material. The heat storage material is dispersed in the heat insulation layer, and after mixing with the hollow particles, when it contacts a high-temperature object, it can simultaneously play the role of heat insulation and heat absorption, and quickly block the transfer of heat.
[0048] The preferred heat storage material of the present invention is dispersed in the sealing layer. When the heat insulation and fireproof material is obtained by the above method 2, the heat storage material and the liquid flame retardant resin are uniformly mixed to form a flame retardant resin liquid of the heat storage material, and then the flame retardant resin liquid is uniformly applied to the upper and lower surfaces of the pre-prepared heat insulation layer, and then dried and solidified at a suitable temperature and cooled at room temperature to form a flame retardant resin cured film with heat storage material powder attached on both sides of the heat insulation layer, respectively, to form a heat insulation and fireproof material with heat storage layers distributed on both sides of the heat insulation layer as one body, and at this time, the heat storage layer is the sealing layer. The flame retardant resin cured film with heat storage material particles attached can not only absorb a large amount of heat, but also solve the problem of hollow particles inside the porous material scattering from the pores of the porous material. The heat storage material is dispersed in the sealing layer, that is, distributed on at least two opposite sides of the heat insulation layer. By adjusting the thickness of the sealing layer, the amount of heat storage material used can be accurately controlled. When in contact with a high-temperature object, the heat storage material dispersed on the outside can be thermally decomposed and absorb heat at the first time to slow down heat transfer. Then, the thermal insulation layer further blocks the heat, while part of the heat continues to be transferred to the heat storage layer far away from the heat source. The heat storage layer continues to decompose thermally to absorb heat, and the effects of heat insulation and heat absorption are most effectively exerted, thereby ensuring that the thermal insulation and fireproofing materials have excellent thermal insulation properties.
[0049] The porous material of the present invention is preferably a fiber structure. The fiber structure refers to an aggregate formed by fibers, such as non-woven fabrics. Among them, non-woven fabrics have a certain thickness, are easy to form a porous structure, and have certain compression rebound properties. If used as a supporting substrate, they have good performance, so they are preferred. The form of the non-woven fabric can be needle-punched, spunlace, etc. Considering the composite processing with aerogel materials, the form of the fiber structure is more preferably a needle-punched non-woven fabric with a porous structure. As a needle-punched non-woven fabric, its needle density is preferably 100 needles / cm 2 The needle density is more preferably 150 needles / cm 2As mentioned above, in the obtained fiber structure, there are more entanglements between the fibers, stronger friction and cohesion, and the overall tensile strength, shear strength and shear modulus are higher. That is, the needle punching density of the non-woven fabric is particularly important. If the needle punching density is too low, the necessary mechanical properties such as tensile and shearing cannot be guaranteed; if the needle punching density is too high, the non-woven fabric layer is repeatedly punctured, not only the processing performance is reduced, the pores contained in the material as a whole become less, the amount of hollow particles attached is reduced, and the fiber strength constituting the non-woven fabric is reduced, which in turn causes the shear performance to decrease. Specifically, according to the ASTM C 273 / C 273M test standard, the shear strength and shear modulus of the heat-insulating and fire-proof material of the present invention are preferably above 1MPa. The heat-insulating and fire-proof material of the present invention is used in batteries. Since the initial interval between the two cells in the battery is relatively fixed, when the battery is in use or charging, a large amount of heat will be generated, the cell will expand due to heat, the thickness will increase, and the interval between the two cells will become narrower. At this time, the fiber structure can provide better compression rebound performance, can absorb the battery core expansion stress, and play a buffering role, that is, the fiber structure of the present invention can be compressed when the battery core is heated and expanded, and can return to its original thickness after the battery core is cooled and contracted. In addition, as a heat-insulating and fire-proof material used between battery cores, the battery cores continuously vibrate and relatively displace during the movement of the car, and drive the heat-insulating and fire-proof material to undergo frictional shearing. Therefore, the heat-insulating and fire-proof material is required to have good shear strength and shear modulus.
[0050] In the fiber structure of the present invention, the pores with a pore size of 5 to 50 μm preferably account for more than 50% of all pores. The porous structure in the fiber structure is conducive to the attachment and fixation of the aerogel powder, thereby giving the fiber structure better thermal insulation. If the pores in the fiber structure are too large, the aerogel powder is easy to scatter and the uniformity of dispersion deteriorates; if the pores in the fiber structure are too small and the surface tension is too large, the aerogel powder is not easy to enter the inside of the pores, the adhesion is poor, and it is easy to scatter and fall when vibrated by external forces. If the ratio of pores between 5 and 50 μm in the fiber structure to all pores is too low, during composite processing, the aerogel powder dispersed in the liquid enters the pores in the fiber structure, and it is very easy to flow and quickly flow out of the pores in the fiber structure, resulting in the aerogel powder being unable to be evenly dispersed and the thermal insulation performance being deteriorated. Considering the difficulty of the aerogel dispersion entering the microstructure and the uniformity of the powder dispersion, the pores with a pore size of 5 to 50 μm in the above-mentioned fiber structure more preferably account for 50 to 95% of all pores.
[0051] At room temperature, the thermal conductivity of the fiber structure in the heat-insulating and fire-proof layer of the present invention is preferably lower than 0.040W / (m·K). As a thermal insulation material between battery cells, as a thermal protection material that can effectively delay or block thermal runaway of battery cells and delay the propagation to the entire battery system, the fiber structure that constitutes its main body must have excellent thermal insulation. If the thermal conductivity of the fiber structure at room temperature is too high, it will not be able to effectively play a thermal insulation role, inhibit heat diffusion, or delay the spread of fire. It is also possible to quickly conduct heat to adjacent battery cells, causing rapid heat transfer, resulting in chain thermal runaway, reducing escape time, and thus causing accidents.
[0052] The fiber structure is preferably a non-woven fabric formed by thermoplastic fibers with an LOI value of more than 28% and non-melting fibers. Thermoplastic fibers with an LOI value of more than 28% include but are not limited to flame-retardant polyester fibers, polyphenylene sulfide fibers, polytetrafluoroethylene fibers, etc. Non-melting fibers include but are not limited to pre-oxidized fibers, glass fibers, phenolic fibers, etc. The non-melting fibers here can be used as a more heat-resistant skeleton support layer, so that the resulting thermal insulation and flame-retardant material maintains a certain shape and can withstand deformation. Among them, the ratio of thermoplastic fibers to non-melting fibers is 10%:90%~80%:20%. If the ratio of thermoplastic fiber to non-melting fiber is too low, it means that the content of thermoplastic fiber is too small to evenly cover the surface of non-melting fiber. When the obtained thermal insulation and fireproof material encounters high temperature, it cannot fully and effectively block large-scale thermal runaway, which propagates from the out-of-control single battery cell to the surrounding battery cells. If the ratio of thermoplastic fiber to non-melting fiber is too high, when the thermal insulation and fireproof material encounters high temperature, the excess thermoplastic fiber will droplet, and the non-melting fiber will be too small, resulting in the inability of thermoplastic fiber to carry the droplet. As a result, the obtained thermal insulation and fireproof material will be perforated by droplets, causing heat or flames to be quickly and directly transmitted to the surrounding battery cells, causing large-scale thermal runaway, and even causing casualties to the driver and passengers.
[0053] The hollow particles of the present invention are preferably aerogel powder. Aerogel powder has a nanoporous structure and extremely low density. As an excellent thermal insulation material, it is widely used in pipelines, ships, motor vehicles, and batteries. However, aerogel has low strength, high brittleness, and poor mechanical properties. If used alone, it cannot exert its thermal insulation properties. Therefore, aerogel powder is attached to the surface of a fiber structure, and the fiber structure itself is formed by criss-crossing fibers to form a porous structure. The porous structure can serve as an attachment substrate for aerogel powder, which can effectively carry aerogel powder, thereby achieving the excellent thermal insulation properties of the material as a whole. The method for attaching aerogel powder to the surface of a fiber structure of the present invention is as follows: first, the fiber structure is immersed in a uniformly dispersed aerogel dispersion liquid, and the aerogel powder with a smaller average diameter dispersed in the liquid enters the interior of the fiber structure with better phase properties. Then, the fiber structure that has fully absorbed the aerogel dispersion liquid is slightly pressurized to remove excess dispersion liquid on the surface, and then low-temperature drying is performed to obtain a composite material of aerogel powder attached to the surface of the fiber structure. Finally, the composite material is packaged and processed, thereby solving the problem of aerogel powder inside the fiber structure scattering from the pores in the fiber structure.
[0054] The weight ratio of aerogel powder in the heat-insulating fireproof material of the present invention is preferably 15% or more. If the weight ratio of aerogel powder is too low, that is, the amount of aerogel powder attached to the fiber structure becomes smaller, or even no aerogel powder is attached to part of the fiber structure, resulting in uneven dispersion of aerogel powder, thereby affecting the uniformity and stability of the thermal insulation performance of the material, and the overall thermal insulation performance of the material is also deteriorated. Considering the processing cost and thermal insulation performance, the weight ratio of aerogel powder in the heat-insulating fireproof material of the present invention is more preferably 20-80%, and further preferably 20-60%.
[0055] Since the hollow particles dispersed in the porous material are small in size and light in specific gravity, they are easily scattered under the action of external force. In order to prevent the problem of the thermal insulation performance of the material from being reduced due to the scattering and falling of the hollow particles, the airtightness of the continuous sheet material located outside the porous material is preferably 20cm 3 / cm 2 / s or less, more preferably 15cm 3 / cm 2 / s or less, and more preferably 10cm 3 / cm 2 / s or less. If the air tightness is too high, the sealing will be poor. When the thermal insulation and fireproofing materials are squeezed or impacted by external forces, the aerogel powder inside the fiber structure will easily fly and fall. The lower the air tightness, the more the aerogel powder can be sealed and fixed in the fiber structure, which can effectively play a role in heat insulation. At the same time, it is also conducive to the mechanical suction cup to transport and assemble the material through negative pressure.
[0056] The above-mentioned continuous sheet material is preferably a film material, a sheet formed by a fiber textile, or a sheet material formed by a continuous resin. When the continuous sheet material is a film material, it is beneficial to the overall lightweight of the thermal insulation and fireproofing material. Any side of the film material may also contain a heat reflective material. The heat reflective material can be a heat reflective coating attached to the surface of the film material, such as thermally evaporated aluminum, etc., or it can be a heat reflective continuous sheet material, such as aluminum foil, etc. The heat reflective material has a relatively obvious heat-resistant effect in reducing heat transfer. The film material can be a polymer film with good high temperature resistance, such as polyphenylene sulfide film, polyimide film, etc., or it can be a conventional polyester film, or it can be a non-high temperature resistant or non-flame retardant film, such as a polyethylene film. In order for the overall thermal insulation and fireproofing material to have excellent flame retardancy, the gram weight of the non-high temperature resistant or non-flame retardant film material is preferably 20g / m 2 Below, more preferably 15g / m 2 The membrane material can be partially melted by heating and then combined with the porous material in the thermal insulation layer; the membrane material can also be combined with the porous material in the thermal insulation layer by an adhesive such as hot melt adhesive powder.
[0057] When the continuous sheet material is a sheet formed of fiber textiles, the fiber textiles are more preferably textiles composed of flame retardant fibers, such as aramid fabrics. The fiber textiles can be in any form, and can be woven fabrics, knitted fabrics, or non-woven fabrics.
[0058] When the continuous sheet material is a sheet material formed of a continuous resin, a coating material with good heat resistance or flame retardancy is preferred, such as ceramic coatings and silicate coatings in inorganic high temperature resistant coatings, and fluororesin coatings and silicone high temperature resistant coatings in organic high temperature resistant coatings.
[0059] The temperature difference between the two sides of the thermal insulation and fireproof material of the present invention is preferably greater than 300°C. That is, when one side of the thermal insulation and fireproof material is in contact with a high-temperature heat source, heat is conducted from the higher temperature heating surface to the lower temperature non-heating surface, and 20 minutes after the heat conduction occurs, the temperature difference between the two sides will be greater than 300°C. When a battery cell located on one side of the thermal insulation and fireproof material has a thermal runaway, its temperature will rise rapidly, and the heat will be quickly transferred to one side of the surface of the thermal insulation and fireproof material. At this time, in order to avoid chain thermal runaway of the battery cell, the thermal insulation and fireproof material must have excellent thermal insulation properties. Within a few minutes of heat transfer, when the temperature difference between the two sides of the material is greater than 300°C, the heat transfer speed can be effectively slowed down, thereby gaining precious escape time for the driver and passengers. If the temperature difference between the two sides of the thermal insulation and fireproof material is too low, when the battery cell heats up, the heat will be quickly conducted to the adjacent battery cell, causing chain thermal runaway in a very short time, thereby endangering the lives of the driver and passengers.
[0060] The compression elasticity of the heat-insulating and fire-proof material of the present invention is 3 to 15%. When the lithium-ion power battery is charged and discharged, a certain internal pressure and deformation will appear inside the battery cell. Therefore, the heat-insulating material placed between the battery cells needs to have a certain compression deformation and recovery force after compression. If the rigidity of the heat-insulating and fire-proof material is large, that is, the compression deformation is small, the internal pressure in the battery cell cannot be released during the charging and discharging process of the battery, causing the battery cell shell to be squeezed and deformed, reducing the life and safety of the battery system; if the heat-insulating pad cannot be restored after compression, the gap between the battery cells will become larger, and the battery cells will loosen and collide during driving, resulting in an increased probability of thermal runaway and a significant reduction in safety.
[0061] The heat-insulating and fire-proofing material of the present invention obtains a heat-insulating layer by composite processing of hollow particles and porous materials, and encapsulates the heat-insulating layer to effectively prevent the hollow particles from scattering and falling, thereby achieving a lightweight heat-insulating and fire-proofing battery cell heat-insulating buffer material with both heat-insulating and fire-proofing properties. The heat-insulating and fire-proofing material can be used in batteries.
[0062] The present invention is further described by the following examples, but the protection scope of the present invention is not limited to the examples. The physical property parameters in the examples are measured by the following methods.
[0063]
Volume density
[0064] Bulk density refers to the ratio of the mass of a material to the sum of the volume of the substance, closed pores and open pores, and is expressed in g / cm 3 . For porous materials with a certain thickness, the unit area weight and thickness of the porous material are measured respectively, and then the volume density of the porous material is calculated by the following formula. The test method of unit area weight: According to JIS L 1096~1999 8.4, use an electronic balance to weigh the weight of a 10cm×10cm sample, and then multiply the obtained data by 100 to obtain the weight of the converted fabric per square meter, measure 5 groups of data, and take the average of the 5 test results as the final test result of the sample; the test method of thickness: According to JIS L 1096~1999 8.5, use a handheld thickness gauge to test the thickness of the sample, measure 5 groups of data, and take the average of the 5 test results as the final test result of the sample. The calculation formula for volume density is as follows:
[0065] Bulk density (g / cm 3 ) = weight per unit area (g / m 2 ) / thickness(mm) / 1000.
[0066] When the porous material has sealing material attached to its surface or contains hollow particles or other particulate matter inside, first peel off the sealing material on the surface, and then use a solvent with high affinity to the hollow particles or other particulate matter to remove the hollow particles or other particulate matter. The following materials can be selected as solvents, such as water, methanol, ethanol, acetone, n-hexane, methyl acetone, etc. You can use one of them or a combination of multiple ones. Any solvent that can prevent the porous material from softening, deforming, or dissolving can be used.
[0067] The cleaning temperature and time can be appropriately selected, but a solvent that does not soften, deform, or dissolve the porous material needs to be selected. In addition, the cleaning can be an immersion treatment, or mechanical action can be added, such as ultrasonic cleaning.
[0068] After washing, the porous material is dried at a temperature and time that does not soften, deform, or melt. The weight of the porous material after the first washing and drying is measured and marked as W. 1 The weight of the porous material after the second washing and drying is measured and marked as W. 2 , when (W 1 -W 2 ) / W 1 When the weight reduction rate of ×100(%) is below 0.5%, it can be considered that the hollow particles and other particulate matter have been completely removed. Then the above method is used to measure the unit area weight and thickness of the porous material, and finally the volume density of the porous material is calculated.
[0069]
Average diameter of hollow particles
[0070] After sampling, the hollow particles were fixed on a sample stage for gold plating. The hollow particles were photographed using a scanning electron microscope (SEM) with a magnification of 1000 times. The diameters of the hollow particles of 50 samples were measured, and the average value of the 50 test results was calculated as the average diameter of the hollow particles.
[0071]
Carbonization treatment
[0072] In an aerobic environment at room temperature, the heat-insulating and fire-proofing material is subjected to a flat-plate heating treatment at a temperature of 600°C. After one side is treated for 15 minutes, the other side is heated for 15 minutes. The heating is then stopped, the treated sample is removed, and the carbonization treatment is completed.
[0073]
Thermal conductivity
[0074] According to the GB / T 10295-2008 test standard, the thermal conductivity of thermal insulation and fireproof materials is measured at 25°C.
[0075]
LOI value
[0076] According to the ISO4589-2-2017 test standard, a KS-653D oxygen index tester is used. At room temperature, a mixture of oxygen and nitrogen at 23°C ± 2°C is introduced, and the thermoplastic fiber is placed in a fixture and exposed to the flame for 30 seconds. The sample is removed every 5 seconds to observe whether it burns. The ignition point temperature of the sample at the lowest oxygen concentration is measured, and this oxygen concentration is the LOI value, which is the limiting oxygen index.
[0077] [The average total thickness of the sealing layer accounts for the proportion of the overall thickness of the thermal insulation and fireproofing materials]
[0078] Use a digital microscope to photograph the cross-section of the sealing layer and the thermal insulation and fireproofing material as a whole, with a shooting magnification of 50 times, and randomly measure the cross-sectional height of 5 locations of the sealing layer and the thermal insulation and fireproofing material as a whole. Take the average value of the 5 test results as the average thickness of the sealing layer and the thermal insulation and fireproofing material. Among them, the sum of the average thickness of the upper and lower sealing layers is recorded as D 1 The average thickness of the fireproof and heat-insulating material is recorded as D 2 The formula for calculating the ratio of the average total thickness of the sealing layer to the overall thickness of the thermal insulation and fireproofing material is as follows: The ratio of the average total thickness of the sealing layer to the overall thickness of the thermal insulation and fireproofing material = D 1 / D 2 ×100%.
[0079] [The ratio of the weight of water released by the thermal storage material when heated to the weight of the thermal insulation and fireproofing material]
[0080] Take a square thermal insulation fireproof material with a size of 8cm×8cm, and place the sample on a heating platform with an area of 10cm×10cm at a temperature of 600℃ for heating treatment. In order to prevent the sample from accidentally melting and contaminating the heating platform, place a square copper plate with a size of 8cm×8cm and a thickness of 1mm on the upper and lower sides of the thermal insulation fireproof material to be tested. The copper plate can conduct heat quickly, so the temperature of the heated surface can be considered to be equal to the temperature of the heating platform. The weight of the thermal insulation fireproof material before heating is measured as M 0 The weight of the heat insulation and fireproofing material after heating to constant weight is M 1 , calculate the ratio of the weight of water released by the thermal storage material when heated to the weight of the thermal insulation and fireproofing material according to the following formula:
[0081] The weight ratio of water to heat insulation and fireproofing materials (%) = (M 0 -M 1 ) / M 0 ×100%.
[0082] [Ratio of the average thickness of the thermal storage layer to the average thickness of the thermal insulation layer]
[0083] The cross-sections of the heat storage layer and the heat insulation layer were photographed with a digital microscope at a magnification of 50 times, and the cross-sectional heights of the heat storage layer and the heat insulation layer were randomly measured at 5 locations, and the average of the 5 test results was taken as the average thickness of the heat storage layer and the heat insulation layer. The sum of the average thickness of the upper and lower heat storage layers is recorded as H. 1 The average thickness of the thermal insulation layer is denoted as H 2 The formula for calculating the ratio of the average total thickness of the heat storage layer to the thermal insulation layer is as follows: The ratio of the average total thickness of the heat storage layer to the overall thickness of the thermal insulation and fireproofing material = H 1 / H 2 ×100%.
[0084] [Pore diameter ratio in fiber structure]
[0085] According to the ASTM F316 test standard, the capillary flow pore meter (PMI for short, CFP-1100-AEX) of Stovwell, USA, was used to test the pore size of the fiber structure. The test principle is: take out the saturated sample to be tested from the wetting liquid, put it into the sample chamber and seal it, and then use gas to flow from the front of the sample to the sample chamber. The gas pressure is controlled by a computer to increase it slowly until it reaches a pressure sufficient to overcome the capillary effect of the liquid corresponding to the maximum pore size, that is, the bubble point pressure. When the pressure increases further, a measurable initial gas flow is formed until the liquid that can flow is emptied. Using a dry sample will also generate flow rate to pressure data, which will be stored and displayed in real time. The calculation of the pore diameter refers to the following formula, and the application program that comes with the device is used to calculate the ratio of pores between 5 and 50 μm, so as to obtain the final test results.
[0086] D = 4γCosθ / p,
[0087] in,
[0088] D = pore diameter,
[0089] γ = surface tension of the liquid,
[0090] θ = contact angle,
[0091] p = pressure difference.
[0092]
Weight ratio of hollow particles
[0093] The porous material without hollow particles attached is weighed and the weight is recorded as S 0 , the weight of the hollow particles after attachment is recorded as S 1 , calculate the weight of the hollow particles as S 1 -S 0 .
[0094] When the porous material to be tested contains hollow particles, weigh the sample and record it as S 1 , and then use a solvent with high affinity to the hollow particles to remove the hollow particles. The following materials can be selected as solvents, such as water, methanol, ethanol, acetone, n-hexane, methyl acetone, etc., and any one of them can be used, or a combination of multiple can be used. Any solvent that can prevent the porous material from softening, deforming, or dissolving can be used.
[0095] The cleaning temperature and time can be appropriately selected, but a solvent that does not soften, deform, or dissolve the porous material needs to be selected. In addition, the cleaning can be an immersion treatment, or mechanical action can be added, such as ultrasonic cleaning.
[0096] After washing, the porous material is dried at a temperature and time that does not soften, deform, or melt. The weight of the porous material after the first washing and drying is measured and marked as A. 1 When the weight of the porous material after the second washing and drying is measured, it is marked as A. 2 , when (A 1 -A 2 ) / A 1 When the weight reduction rate of ×100(%) is below 0.5%, it can be considered that the hollow particles have been completely removed. The weight of the sample at this time is weighed and recorded as S 0 , calculate the weight of the hollow particles as S 1 -S 0 , the calculation formula of the weight ratio of hollow particles is as follows:
[0097] Weight ratio of hollow particles (%) = (S 1 -S 0 ) / S 0 ×100%.
[0098]
Air tightness of continuous sheet materials
[0099] According to JIS L 1096A method, a continuous sheet material is placed on an air permeability tester and its air permeability is tested under a pressure difference of 125 Pa. N=5 samples are randomly selected for testing, and the average of the test results is taken as the final air tightness test result.
[0100] [Temperature difference between the two sides of thermal insulation and fireproof materials]
[0101] The heat insulation and fireproof material is placed on a heating platform that has been stably heated. The set temperature of the heating platform after stabilization is 600℃, which is recorded as T 1 , test the temperature change of the heated side of the thermal insulation and fireproof material, and take the highest temperature within 20 minutes of the test, recorded as T 2 , the calculation of the temperature difference between the two sides of the thermal insulation and fireproofing material is as follows:
[0102] Temperature difference between the two sides of the thermal insulation and fireproofing material (℃) = T 1 -T 2 .
[0103]
Thermal insulation
[0104] The greater the temperature difference between the two sides of the thermal insulation and fireproofing material, the better the thermal insulation. If the temperature difference between the two sides of the thermal insulation and fireproofing material is greater than 400°C, it is judged as excellent, recorded as S; if the temperature difference between the two sides of the thermal insulation and fireproofing material is 300°C to 400°C, it is judged as good, recorded as A; if the temperature difference between the two sides of the thermal insulation and fireproofing material is greater than or equal to 250°C and less than 300°C, it is judged as fair, recorded as B; if the temperature difference between the two sides of the thermal insulation and fireproofing material is less than 250°C, it is judged as poor, recorded as F.
[0105]
Compression elasticity
[0106] Using SE-15 compression elasticity testing machine, in standard mode, measure the sample thickness T when the pressure is 0.3MPa. 1 Then pressurize to 2MPa, and test the thickness T after one minute. 2 Then remove the pressure and let it stand for one minute, and then measure the sample thickness T when the pressure is increased to 0.3MPa again. 3 , accurate to 0.01mm. Calculate the compression elasticity according to the following formula: Compression elasticity (%) = (T 3 -T 2 ) / (T 1 -T 2 )×100%.
[0107] Before describing the following examples, the materials involved in the examples are described in detail.
[0108] [Fibers that make up porous materials]
[0109] <Non-melting fiber>
[0110] The pre-oxidized fiber "Pyron" (registered trademark in the United States) produced by Zoltek was used, with a length of 50 mm, a fineness of 1.7 dtex, a high-temperature shrinkage rate of 1.6%, and a room-temperature thermal conductivity of 0.033 W / (m·K) (the weight was 200 g / m 2 , needle-punched felt with a thickness of 2 mm).
[0111] <Thermoplastic Fiber>
[0112] The polyphenylene sulfide fiber "TORCON" (registered trademark) produced by Toray Industries, Ltd. has a single fiber diameter of 2.2 dtex (diameter of 14.5 microns), a length of 51 mm, a product name of S371, an LOI of 34%, a melting point of 284°C, a glass transition temperature of 90°C, a crimp number of 14 (pieces / 25mm), and a crimp ratio of 15%.
[0113]
Hollow particles
[0114] The aerogel powder produced by Shenzhen Zhongning Technology Co., Ltd. is AG-D. The thermal conductivity of the aerogel powder at room temperature is 0.018W / (m·K), the porosity is 90%, and the specific surface area is 800m 2 / g.
[0115]
Heat storage material
[0116] The flame retardant grade aluminum hydroxide powder produced by Yangzhou Dilan Chemical Raw Materials Co., Ltd. is used, the effective component of aluminum hydroxide is more than 99.6% by weight, and the attached water content is less than 0.8% by weight.
[0117]
Sealing layer
[0118] A black opaque polyimide film is used, with a light transmittance of less than 1%, a heat shrinkage of less than 0.1%, and a moisture absorption rate of less than 2%.
[0119] Example 1
[0120] 60 wt% of polyphenylene sulfide fiber with LOI value of 34% and 40 wt% of pre-oxidized fiber were blended, carded, laid, and then needle punched at a density of 400 needles / cm 2 Needle punching was performed under the condition of 1.0 mm thick and 300 g / cm 3 , volume density is 0.30g / cm 3 The needle-punched nonwoven fabric is used as the fiber structure, and the thermal conductivity of the fiber structure is measured to be 0.037W / (m·K), and the pores with a pore size between 5 and 50μm in the fiber structure account for 85% of all the pores; the needle-punched nonwoven fabric prepared as above is immersed in a uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion is slightly pressurized to remove excess dispersion on the surface, and then low-temperature drying is performed to obtain a composite material with an average diameter of 50 microns of aerogel powder attached to the inside and surface of the needle-punched nonwoven fabric as a thermal insulation layer, and the weight ratio of the aerogel powder is measured to be 17%; after mixing aluminum hydroxide powder with polyethylene hot melt adhesive particles, the mixed particles are evenly spread on the upper and lower sides of the prepared thermal insulation layer in a sprinkled manner to form a layer of aluminum hydroxide powder in the form of a film, which is the heat storage layer; and then an airtightness of 0.5cm is used. 3 / cm 2 / s, a polyimide film with a thickness of 50 microns was encapsulated from six sides, and the sealing material was fixed to the outer surface of the insulation layer by heating and pressurizing, and finally a thermal insulation and fireproof material was obtained. Its various physical properties were evaluated and shown in Table 1.
[0121] Example 2
[0122] 60 wt% of polyphenylene sulfide fiber with LOI value of 34% and 40 wt% of pre-oxidized fiber were blended, carded, laid, and then needle punched at a density of 300 needles / cm 2 Needle punching was performed under the condition of 1.5 mm thick and 300 g / cm 3 , volume density is 0.20g / cm 3 The needle-punched nonwoven fabric is used as the fiber structure, and the thermal conductivity of the fiber structure is measured to be 0.035W / (m·K), and the pores with a pore size of 5 to 50μm in the fiber structure account for 60% of all the pores; the needle-punched nonwoven fabric prepared above is immersed in the uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion is slightly pressurized, the excess dispersion on the surface is removed, and then low-temperature drying is performed to obtain a composite material with an average diameter of 50 microns of aerogel powder attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the aerogel powder is measured to be 24%. The rest is the same as Example 1, and finally the heat insulation and fireproof material of the present invention is obtained, and its various physical properties are evaluated and shown in Table 1.
[0123] Example 3
[0124] 60 wt% of polyphenylene sulfide fiber with LOI value of 34% and 40 wt% of pre-oxidized fiber were blended, carded, laid, and then needle punched at a density of 150 needles / cm 2 Needle punching was performed under the condition of 4.2mm thickness and 300g / cm 3 , volume density is 0.07g / cm 3 The needle-punched nonwoven fabric is used as the fiber structure, and the thermal conductivity of the fiber structure is measured to be 0.033W / (m·K), and the pores with a pore size of 5 to 50μm in the fiber structure account for 35% of all the pores; the needle-punched nonwoven fabric prepared above is immersed in the uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion is slightly pressurized, the excess dispersion on the surface is removed, and then low-temperature drying is performed to obtain a composite material with an average diameter of 50 microns of aerogel powder attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the aerogel powder is measured to be 43%. The rest is the same as Example 1, and finally the heat insulation and fireproof material of the present invention is obtained, and its various physical properties are evaluated and shown in Table 1.
[0125] Example 4
[0126] After mixing aluminum hydroxide powder with polyethylene hot melt adhesive particles, the mixed particles are evenly spread on the upper and lower sides of the prepared insulation layer in the form of a film to form a layer of aluminum hydroxide powder, which is the heat storage layer; then the air tightness is 0.1cm 3 / cm 2 / s, a polyimide film with a thickness of 80 microns is encapsulated from six sides, and the sealing material is fixed to the outer surface of the insulation layer by heating and pressurizing. The rest is the same as in Example 1, and finally a heat-insulating and fire-proof material is obtained. Its various properties are evaluated and shown in Table 1.
[0127] Example 5
[0128] Aluminum hydroxide powder and liquid polyimide flame retardant resin are uniformly mixed to form a flame retardant resin liquid containing aluminum hydroxide, which is then uniformly coated on the upper and lower surfaces of the needle-punched non-woven fabric, dried and cured at 170°C and then cooled at room temperature to form a layer of polyimide flame retardant resin cured film with aluminum hydroxide powder attached on the upper and lower surfaces of the needle-punched non-woven fabric as a heat storage layer, and finally a heat insulation and fireproof material with heat storage layers distributed on both sides of the heat insulation layer as one body is obtained, and at this time, the heat storage layer is a sealing layer. The rest is the same as in Example 2. Its various physical properties are evaluated and shown in Table 1.
[0129] Example 6
[0130] Aluminum hydroxide powder is sprinkled into the composite material of needle-punched nonwoven fabric and aerogel by physical filling to obtain a heat insulation layer. At this time, the heat insulation layer is the heat storage layer. The preparation method of the composite material is the same as that of Example 2. Then, an airtightness of 0.5 cm 3 / cm 2 / s, a polyimide film with a thickness of 50 microns is encapsulated from six sides, and the sealing material is fixed to the outer surface of the insulation layer by heating and pressurizing, and finally the thermal insulation and fireproof material of the present invention is obtained. Its various physical properties are evaluated and shown in Table 1.
[0131] Example 7
[0132] Aluminum hydroxide powder and liquid polyimide flame retardant resin are uniformly mixed to form a flame retardant resin liquid containing aluminum hydroxide, which is then uniformly coated on the upper and lower surfaces of the needle-punched non-woven fabric, dried and cured at 170°C and then cooled at room temperature to form a layer of polyimide acid flame retardant resin cured film with aluminum hydroxide powder attached on the upper and lower surfaces of the needle-punched non-woven fabric as a heat storage layer, and finally a heat insulation and fireproof material with heat storage layers distributed on both sides of the heat insulation layer as one body is obtained, and at this time, the heat storage layer is a sealing layer. The rest is the same as in Example 2. Its various physical properties are evaluated and shown in Table 1.
[0133] Example 8
[0134] Aluminum hydroxide powder and liquid polyimide flame retardant resin are uniformly mixed to form a flame retardant resin liquid containing aluminum hydroxide, which is then uniformly coated on the upper and lower surfaces of the needle-punched non-woven fabric, dried and cured at 170°C and then cooled at room temperature to form a layer of polyimide acid flame retardant resin cured film with aluminum hydroxide powder attached on the upper and lower surfaces of the needle-punched non-woven fabric as a heat storage layer, and finally a heat insulation and fireproof material with heat storage layers distributed on both sides of the heat insulation layer as one body is obtained, and at this time, the heat storage layer is a sealing layer. The rest is the same as in Example 1. Its various physical properties are evaluated and shown in Table 1.
[0135] Example 9
[0136] 60 wt% of polyphenylene sulfide fiber with LOI value of 34% and 40 wt% of pre-oxidized fiber were blended, carded, laid, and then needle punched at a density of 400 needles / cm 2 Needle punching was performed under the condition of 1.0 mm thick and 300 g / cm 3 , volume density is 0.30g / cm 3 The needle-punched nonwoven fabric is used as the fiber structure, and the thermal conductivity of the fiber structure is measured to be 0.037W / (m·K), and the pores with a pore size between 5 and 50μm in the fiber structure account for 85% of all the pores; the needle-punched nonwoven fabric prepared as above is immersed in a uniformly dispersed hollow glass microbead dispersion, and then the fiber structure after fully absorbing the hollow glass microbead dispersion is slightly pressurized to remove excess dispersion on the surface, and then low-temperature drying is performed to obtain a composite material in which hollow glass microbead powder with an average diameter of 1000 microns is attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the hollow glass microbead powder is measured to be 17%; after mixing magnesium hydroxide powder with polyethylene hot melt adhesive particles, the mixed particles are evenly spread on the upper and lower sides of the prepared heat insulation layer in a sprinkled manner to form a layer of magnesium hydroxide powder in the form of a film, which is the heat storage layer; and then an airtightness of 0.5cm is used. 3 / cm 2 / s, a polyimide film with a thickness of 50 microns was sealed on four sides from the top, bottom surface, front and rear sides, and the sealing material was fixed to the outer surface of the insulation layer by heating and pressurizing, and finally a thermal insulation and fireproof material was obtained. Its various physical properties were evaluated and shown in Table 1.
[0137] Example 10
[0138] After mixing sodium sulfate decahydrate powder with polyethylene hot melt adhesive particles, the mixed particles are evenly spread on the upper and lower sides of the prepared insulation layer in the form of a film to form a layer of sodium sulfate decahydrate powder, which is the heat storage layer; then the airtightness is 0.5cm 3 / cm 2 / s, a polyimide film with a thickness of 50 microns is sealed on four sides from the top, bottom surface and front and rear sides, and the sealing material is fixed to the outer surface of the thermal insulation layer by heating and pressurizing. The rest is the same as Example 9, and finally a thermal insulation and fireproof material is obtained. Its various properties are evaluated and shown in Table 1.
[0139] Embodiment 11
[0140] After mixing potassium aluminum sulfate dodecahydrate powder with polyethylene hot melt adhesive particles, the mixed particles are evenly spread on the upper and lower sides of the prepared insulation layer in the form of a film to form a layer of potassium aluminum sulfate dodecahydrate powder layer, which is the heat storage layer; then the airtightness is 0.5cm 3 / cm 2 / s, a polyimide film with a thickness of 50 microns is sealed on four sides from the top, bottom surface and front and rear sides, and the sealing material is fixed to the outer surface of the insulation layer by heating and pressurizing. The rest is the same as Example 9, and finally a thermal insulation and fireproof material is obtained. Its physical properties are evaluated and shown in Table 2.
[0141] Example 12
[0142] The needle-punched nonwoven fabric prepared in Example 1 was immersed in the uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion was slightly pressurized to remove the excess dispersion on the surface, and then low-temperature drying was performed to obtain a composite material with an average diameter of 500 microns of aerogel powder attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the aerogel powder was measured to be 17%. The rest was the same as in Example 1, and finally the heat insulation and fireproof material of the present invention was obtained, and its various physical properties were evaluated and shown in Table 2.
[0143] Embodiment 13
[0144] The needle-punched nonwoven fabric prepared in Example 1 was immersed in the uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion was slightly pressurized to remove the excess dispersion on the surface, and then low-temperature drying was performed to obtain a composite material with an average diameter of 1000 microns of aerogel powder attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the aerogel powder was measured to be 17%. The rest was the same as in Example 1, and finally the heat insulation and fireproof material of the present invention was obtained, and its various physical properties were evaluated and shown in Table 2.
[0145] Embodiment 14
[0146] The needle-punched nonwoven fabric prepared in Example 1 was immersed in the uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion was slightly pressurized to remove the excess dispersion on the surface, and then low-temperature drying was performed to obtain a composite material with aerogel powder with an average diameter of 50 microns attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the aerogel powder was measured to be 12%. The rest was the same as in Example 1, and finally the heat insulation and fireproof material of the present invention was obtained, and its various physical properties were evaluated and shown in Table 2.
[0147] Embodiment 15
[0148] 60 wt% of flame-retardant viscose fiber with an LOI value of 28% and 40 wt% of glass fiber are blended, carded, laid, and then needle-punched at a density of 150 needles / cm 2 Needle punching was performed under the condition of 1.0 mm thick and 300 g / cm 3 , volume density is 0.30g / cm 3 The needle-punched nonwoven fabric of the present invention was used as the fiber structure, and the thermal conductivity of the fiber structure was measured to be 0.037 W / (m·K), and the pores with a pore size of 5 to 50 μm in the fiber structure accounted for 45% of all the pores. The rest was the same as in Example 1. The various physical properties of the heat insulating and fireproofing material of the present invention were evaluated and are shown in Table 2.
[0149] Example 16
[0150] 60 wt% of flame-retardant viscose fiber with an LOI value of 34% and 40 wt% of glass fiber are blended, carded, laid, and then needled at a density of 400 needles / cm 2 Needle punching was performed under the condition of 1.0 mm thick and 300 g / cm 3 , volume density is 0.30g / cm 3 The needle-punched nonwoven fabric of the present invention was used as the fiber structure, and the thermal conductivity of the fiber structure was measured to be 0.032 W / (m·K), and the pores with a pore size of 5 to 50 μm in the fiber structure accounted for 85% of all pores. The rest was the same as in Example 1. The various physical properties of the heat insulating and fireproofing material of the present invention were evaluated and are shown in Table 2.
[0151] Embodiment 17
[0152] Polyphenylene sulfide filaments and glass fibers are woven to produce a 1.9mm thick, 420g / cm2 3 , volume density is 0.22g / cm 3The warp knitted spacer fabric is used as a fiber structure, and the thermal conductivity of the fiber structure is measured to be 0.042W / (m·K). The pores with a pore size of 5 to 50μm in the fiber structure account for 58% of all pores. The warp knitted spacer fabric prepared above is immersed in a uniformly dispersed aerogel dispersion, and then the fiber structure that has fully absorbed the aerogel dispersion is slightly pressurized to remove excess dispersion on the surface, and then low-temperature drying is performed to obtain a composite material with an average diameter of 50 microns of aerogel powder attached to the inside and surface of the warp knitted spacer fabric as a thermal insulation layer. The weight ratio of the aerogel powder is measured to be 25%. Then, an airtightness of 0.5cm is used. 3 / cm 2 / s, a polyimide film with a thickness of 50 microns was encapsulated from six sides, and the sealing material was fixed to the outer surface of the insulation layer by heating and pressurizing, and finally a thermal insulation and fireproof material was obtained. Its various physical properties were evaluated and shown in Table 2.
[0153] Embodiment 18
[0154] The preparation method of the heat insulation layer is the same as that of Example 1. The obtained heat insulation layer is the heat insulation and fireproof material of the present invention. Its various properties are evaluated and shown in Table 2.
[0155] The heat-insulating and fire-proof materials prepared in Examples 1 to 18 are applied to power batteries.
[0156] Comparative Example 1
[0157] 60 wt% of polyphenylene sulfide fiber with LOI value of 34% and 40 wt% of pre-oxidized fiber were blended, carded, laid, and then needle punched at a density of 600 needles / cm 2 Needle punching was performed under the condition of 0.6mm thickness and 300g / cm 3 , volume density is 0.50g / cm 3 The needle-punched nonwoven fabric is used as a fiber structure, and the thermal conductivity of the fiber structure is measured to be 0.051W / (m·K), and the pores with a pore size of 5 to 50μm in the fiber structure account for 96% of all pores; the needle-punched nonwoven fabric prepared above is immersed in a uniformly dispersed aerogel dispersion, and then the fiber structure after fully absorbing the aerogel dispersion is slightly pressurized, and the excess dispersion on the surface is removed, and then low-temperature drying is performed to obtain a composite material with an average diameter of 50 microns of aerogel powder attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the aerogel powder is measured to be 5%. The rest is the same as Example 1. The various physical properties of the material are evaluated and are shown in Table 3.
[0158] Comparative Example 2
[0159] The needle-punched nonwoven fabric prepared in Example 9 was immersed in a uniformly dispersed hollow glass microbead dispersion, and then the fiber structure that fully absorbed the hollow glass microbead dispersion was slightly pressurized to remove excess dispersion on the surface, and then low-temperature drying was performed to obtain a composite material with hollow glass microbead powder with an average diameter of 1500 microns attached to the inside and surface of the needle-punched nonwoven fabric as a heat insulation layer, and the weight ratio of the hollow glass microbead powder was measured to be 17%. The rest was the same as Example 9. The various physical properties of the material were evaluated and are shown in Table 3.
[0160] Comparative Example 3
[0161] Aerogel powder with an average diameter of 50 microns was piled into a 1.4 mm thick cuboid and fixed on a 0.5 cm airtight 3 / cm 2 / s, and a polyimide film with a thickness of 50 microns. The rest is the same as in Example 1, and finally a heat insulation and fireproof material is obtained. Its various properties are evaluated and shown in Table 3.
[0162] Comparative Example 4
[0163] 60 wt% of polyphenylene sulfide fiber with LOI value of 34% and 40 wt% of pre-oxidized fiber were blended, carded, laid, and then needle punched at a density of 400 needles / cm 2 Needle punching was performed under the condition of 1.0 mm thick and 300 g / cm 3 , volume density is 0.30g / cm 3 The needle-punched nonwoven fabric was used as the fiber structure, and the thermal conductivity of the fiber structure was measured to be 0.037 W / (m·K). The pores with a pore size of 5 to 50 μm in the fiber structure accounted for 85% of all the pores. The needle-punched nonwoven fabric obtained above was used as the thermal insulation layer; the preparation method of the heat storage layer and the sealing layer was the same as in Example 1, and finally a thermal insulation and fireproof material was obtained. Its physical properties were evaluated and shown in Table 3.
[0164] Table 1
[0165]
[0166] Table 2
[0167]
[0168] Table 3
[0169]
[0170] According to the above table:
[0171] (1) It can be seen from Examples 1-3 that, under the same conditions, the smaller the volume density of the porous material, the greater the weight ratio of the hollow particles in the thermal insulation layer, and the better the thermal insulation properties of the resulting thermal insulation and fireproofing material.
[0172] (2) It can be seen from Example 5 and Example 7 that, under the same conditions, the average total thickness of the sealing layer of the latter accounts for a proportion of the overall thickness of the thermal insulation and fireproofing material within a further preferred range, and compared with the former, the thermal insulation and fireproofing material obtained has better thermal insulation properties.
[0173] (3) It can be seen from Example 1 and Example 4 that, under the same conditions, the ratio of the average thickness of the heat storage layer to the average thickness of the heat insulation layer of the former is within a more preferred range, and compared with the latter, the heat insulation and fireproofing material obtained has better heat insulation properties.
[0174] (4) It can be seen from Examples 9-11 that, under the same conditions, the weight ratio of the water released by the heat storage material when heated in Example 9 relative to the weight ratio of the heat insulating and fireproofing material is not within the preferred range, and the heat insulating property of the obtained heat insulating and fireproofing material is slightly low.
[0175] (5) It can be seen from Examples 1, 12, and 13 that, under the same conditions, the larger the average diameter of the aerogel, the more voids there are in the resulting thermal insulation and fireproof material, and the thermal insulation is slightly lower.
[0176] (6) It can be seen from Example 1 and Example 14 that, under the same conditions, the aerogel weight ratio of the former is within the preferred range, and compared with the latter, the thermal insulation and fireproofing material obtained has better thermal insulation properties.
[0177] (7) It can be seen from Example 15 and Example 16 that, under the same conditions, the pore size ratio of the fiber structure of the latter is within the preferred range, and compared with the former, the thermal insulation and fireproofing material obtained has better thermal insulation properties.
[0178] (8) It can be seen from Comparative Example 1 and Example 1 that, under the same conditions, the volume density of the porous material in the former is too large, the weight ratio of the aerogel in the thermal insulation layer decreases sharply, and the thermal insulation property deteriorates.
[0179] (9) It can be seen from Comparative Example 2 and Example 9 that, under the same conditions, the average diameter of the hollow glass microspheres in the former is too large, the voids in the obtained material are more, and the thermal insulation property is poor.
[0180] (10) In Comparative Example 3, there is no porous material, and the aerogel powder cannot be stably supported by the substrate, resulting in powder falling off or uneven thermal insulation, and the thermal insulation property deteriorates.
[0181] (11) Comparative Example 4 has no hollow fine particles and cannot block heat transfer, resulting in poor thermal insulation.
Claims
1. A heat-insulating and fire-proof material, characterized in that: The heat-insulating fireproof material at least comprises a heat-insulating layer, the heat-insulating layer comprises a porous material and hollow particles, and the volume density of the porous material is 0.05 to 0.30 g / cm 3 The average diameter of the hollow particles is 30 to 1000 μm, the thermal conductivity of the heat insulating and fireproofing material after carbonization is less than 0.040 W / (m・K) at room temperature, the porous material is a fiber structure, and the fiber structure is a non-woven fabric formed by thermoplastic fibers with an LOI value of more than 28% and non-melting fibers.
2. The heat-insulating and fire-proofing material according to claim 1, characterized in that: The heat insulating fireproof material contains a sealing layer, which is a continuous sheet material. The sealing layer is located on at least two opposite sides of the heat insulating layer, and the average total thickness of the sealing layer accounts for 0.5-90.0% of the overall thickness of the heat insulating fireproof material.
3. The heat-insulating and fire-proofing material according to claim 1 or 2, characterized in that: The heat-insulating fireproof material contains a heat storage material, which is a hydrate or a metal hydroxide. The weight of water released by the heat storage material when heated is in a ratio of 2.0 to 25.0% relative to the weight of the heat-insulating fireproof material.
4. The heat-insulating and fire-proofing material according to claim 3, characterized in that: The heat storage material is a layered structure and is distributed on two opposite sides of the heat insulation layer to form a heat storage layer. The ratio of the average thickness of the heat storage layer to the average thickness of the heat insulation layer is 10-90%.
5. The heat-insulating and fire-proofing material according to claim 3, characterized in that: The heat storage material is dispersed in the heat insulation layer.
6. The heat-insulating and fire-proofing material according to claim 3, characterized in that: The heat storage material is dispersed in the sealing layer.
7. The heat-insulating and fire-proofing material according to claim 1, characterized in that: In the fiber structure, pores with a pore size between 5 and 50 μm account for more than 50% of all pores.
8. The heat-insulating and fire-proofing material according to claim 1 or 7, characterized in that: At room temperature, the thermal conductivity of the fiber structure is lower than 0.040 W / (m·K).
9. The heat-insulating and fire-proofing material according to claim 1, characterized in that: The hollow particles are aerogel powder.
10. The heat-insulating and fire-proofing material according to claim 9, characterized in that: The weight ratio of aerogel powder in the thermal insulation and fireproof material is more than 15%.
11. The heat-insulating and fire-proofing material according to claim 2, characterized in that: The air tightness of the continuous sheet material is 20cm 3 / cm 2 / s or less.
12. The heat-insulating and fire-proofing material according to claim 11, characterized in that: The continuous sheet material is a film-like material, a sheet material formed of a fiber textile, or a sheet material formed of a continuous resin.
13. The heat-insulating and fire-proofing material according to claim 1, characterized in that: The temperature difference between the two surfaces of the heat-insulating and fire-proofing material is greater than 300°C.
14. Use of the heat insulating and fireproof material according to any one of claims 1 to 13 in a battery.
Citation Information
Cited By
Aerogel composite
US12551859B1
